Impact of biodiesel blend mandate (810) on the Malaysian Palm Oil Industry - Shri Dewi A/P Applanaidu; Anizah Md. Ali; Mohammad Haji Alias (Penerbit Universiti Kebangsaan Malaysia, 2014)
Over the last ten years biofuels production has increased dramatically. One of the main factors is the rise in world oil prices, coupledwith heightened interest in tlle abatetnent ofgreenhouse gas emissions and concerns about energt security. The increment in production has been driven by governmental interventions. In the US, the worldb largestfuel ethanol producer, strongfinancial incentives are guaranteedfor biofuel manufacturers. While, in the European (Jnion, the worldb largest biodiesel producer, biofuel consumption is mostly driven by blending mandates in both France and Germany. In the case of Malaysia, biodiesel started to be exported since 2006. The policy mandate of B5 blend of palm oil based biodiesel into diesel in all government vehicles was implemented in February 2009. h is expected that the blend of 85 will be increased to B l0 in future. This paper seeles to examine the impact of B l0 on the Malaysian palm oil market. A structural econometric model consisting of eight structural equations and four identities was proposed in this study. The model has been estimated by two stdge least squares method using annual data for the period 1976- 201 l. The specification ofthe structural model is based on a series ofassumptions about general economic conditions, agricultural policies and technological change. The study indicates that counterfactual simulation ofan increasefrom 85 to B l0 predicts a positive increase (23.31 per cent) in palm oil domestic consumption, 109.3 per cent decrease in stock, 0.07 per cent increase in domestic price of palm oil and a marginal (0.05 percent) increase in production. An increase in domestic demand would make Malaysia more competitive regionally and globally with benefits accruing to all Malaysians.